2010
DOI: 10.1177/0042098009359030
|View full text |Cite
|
Sign up to set email alerts
|

Class Transformation and Work-Life Balance in Urban Britain: The Case of Manchester

Abstract: Recent years have seen an expansion in the work on the attitudes, beliefs and preferences of those middle class groups that that have accompanied the return of capital to many North American and Western European city centres and their surrounding urban suburbs. Yet despite this, we argue that there is little research linking gentrification to wider processes of social transformation, particularly debates over housing market decision-making, the balancing of work and life, and the gender division of labour with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…They are negotiating their role as a professional worker and what a good mother should do (Duncan, Edwards, Reynolds, & Alldred, 2003). This resonates strongly with other studies that have pointed out the complex negotiations of these roles in the every lives of professional women in the context of the gentrifying city (McDowell, Ward, Fagan, Perrons, & Ray, 2006;Schwanen, 2007;Ward, Fagan, McDowell, Perrons, & Ray, 2010). The fierceness of the debate around cargo-bike mums attests to the resistance one provokes when deviating from the norm: In this case, dominant ideas about motherhood in the Dutch context in which mother are the primary care givers and only rarely occupy managerial and other high-paid positions (De Meester et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…They are negotiating their role as a professional worker and what a good mother should do (Duncan, Edwards, Reynolds, & Alldred, 2003). This resonates strongly with other studies that have pointed out the complex negotiations of these roles in the every lives of professional women in the context of the gentrifying city (McDowell, Ward, Fagan, Perrons, & Ray, 2006;Schwanen, 2007;Ward, Fagan, McDowell, Perrons, & Ray, 2010). The fierceness of the debate around cargo-bike mums attests to the resistance one provokes when deviating from the norm: In this case, dominant ideas about motherhood in the Dutch context in which mother are the primary care givers and only rarely occupy managerial and other high-paid positions (De Meester et al, 2011).…”
Section: Discussionsupporting
confidence: 78%
“…To examine experiences of gentrification among older people, this article draws on a study which included the Manchester neighbourhood of Chorlton, the subject of previous research by Savage et al (2005) and Ward et al (2010). The next section discusses the methodology of the research, focusing on the training of older people as co-researchers; the demographic and social characteristics of the neighbourhood; and details of the sample of older people interviewed.…”
Section: Gentrification and 'Place Attachment'mentioning
confidence: 99%
“…The findings discussed here are consistent with related research which highlights the practical and emotional difficulties involved in negotiating the gendered nature of the work-care nexus. In particular, they reveal gendered inequalities in the allocation of domestic tasks, the psychological consequences borne by women as a result of combining dual roles, and the 'invisible' responsibilities of organization and planning which mostly fall to women (Duncan et al, 2003;Fagan et al, 2008;Gatrell, 2005;Hochschild, 1990;Van der Lippe and Peters, 2007;Ward et al, 2010). Going further theoretically than previous studies, we have found Zygmunt Bauman's writing on order and disorder useful for understanding our findings and locating our interviewees' attempts to manage dual spheres within the wider neoliberal economic and political context.…”
Section: Introductionmentioning
confidence: 99%